Parasagittal and parafalcine meningiomas: integral strategy for optimizing safety and retrospective review of a single surgeon series. (2nd September 2020) - Eichberg, Daniel G.; Casabella, Amanda M.; Menaker, Simon A.; Shah, Ashish H.; Komotar, Ricardo J.
Abstract: Background: Parafalcine and parasagittal meningiomas present unique challenges for resection. Although maximal safe resection is the primary goal of surgical management for these lesions, venous infarction and eloquent cortical structure damage occur in up to 14% of cases. Therefore, optimal preoperative planning and intraoperative technique is critical. Methods: We retrospectively reviewed a single surgeon's case series with resection of 58 parafalcine and parasagittal meningiomas. Operative strategy included not crossing the superior sagittal sinus (SSS) during craniotomy, not resecting the falx, use of motor evoked potentials (MEPs) to avoid damage to eloquent brain, and selective use of preoperative embolization. Results: Fifty-eight patients, 45 with parasagittal meningiomas and 13 with parafalcine meningiomas were evaluated. Median age 58.34 years and mean follow-up was 7.7 months. Gross total resection (GTR) was achieved in 51.7% of patients and near-gross total resection rate was 48.3%. Postoperative day one discharge rate was 62.1%. Complication rate was 8.6%, with new postoperative neurologic deficit rate of 5.2%. Tumor recurrence/growth documented on postoperative imaging rate was 3.4%. Conclusions: In our series of parasagittal and parafalcine meningioma resection, we report a 51.7% GTR rate associated with a low complication rate. Techniques to minimize perioperative morbidity include not crossing the SSS on craniotomy, avoiding falx resection, using MEPs, and selective preoperative embolization to optimize the chance of a maximal safe resection. We utilize a strategy of conservative initial tumor resection focused on maximizing the chances of a favorable neurologic outcome, followed as necessary by adjuvant therapies such as radiosurgery and salvage therapies such as laser interstitial thermal therapy, although longer follow-up comparable to that of series with more radical approaches is required to determine if long term outcomes are comparable.